Restrukturisasi Kognitif sebagai Upaya Preventif dan Kuratif terhadap Perilaku Self-injury Siswa SMK - Mustang, Nur Dhian; Saman, Abdul; Amirullah, Muhammad (Universitas Negeri Makassar, 2025)
This study aims to examine the effect of cognitive restructuring techniques in reducing self-injurious behavior among students at State Vocational High School XYZ. The research employed a quantitative approach with a quasi-experimental design using a non-equivalent control group. The sample consisted of ten students selected purposively based on indications of self-injurious behavior, divided into two groups: five students in the experimental group and five in the control group. Data were collected through non-participant observation and a self-injury behavior scale, and analyzed using the Mann-Whitney test. The results revealed a significant decrease in self-injurious behavior scores in the experimental group after receiving cognitive restructuring intervention, shifting from a high to a low category, while the control group showed no meaningful change. Statistical analysis indicated a significance value of 0.009, confirming a significant difference between the two groups. These findings demonstrate that cognitive restructuring techniques are effective in helping students identify, challenge, and modify negative thought patterns that trigger self-injurious behavior, thereby enabling them to develop more adaptive and healthy coping strategies in managing emotional distress.